Distribution Patterns of Soil Insects Across Microhabitat Types in Lemor Botanical Garden, East Lombok, Indonesia - Suliati, Suliati; Artyasa, I Putu; Ilhamdi, Mohammad Liwa (Jurnal Biologi Tropis, 2025)
Soil insects play an important role as indicators of ecosystem balance, however information about soil insects especially the distribution patterns of soil insects across microhabitat in the Lemor Botanical Gardens is still limited. This research aimed to analyze the distribution patterns of soil insects across various types of microhabitats in the Lemor Botanical Garden. This type of research is descriptive exploratif where soil insect samples were taken using the pitfall traf method, soil drill and continued using berlese tullgren. Sampling was carried out for 3 repetitions at two stations, namely station 1 in the Ex Situ area and station 2 in the In Situ area of the Lemor Botanical Garden. Each station consists of 10 sampling plots where each plot consists of 3 microhabitats namely litter, soil surface and subsurface. The research data were analyzed using the Morisita Index. The results indicated that the distribution of soil insects showed variation across microhabitats: in the litter microhabitat, 14% of individuals exhibited a clumped distribution and 1% an uniform distribution; in the soil surface microhabitat, 32% were clumped and 2% uniform distributed; and subsurface microhabitats, 7%  were clumped and 1% uniform distributed. These findings suggest that the dominant distribution pattern of soil insects across all microhabitats is clumped followed by a lesser degree of uniform distribution. The research is expected to provide insights to the public regarding the distribution patterns of soil insects across various types of microhabitats in the Lemor Botanical Garden.